EZ 200 EBARA PUMP MODELING USING CFD FLUENT - IBRAHIM HADI (NIM : 13104145); Pembimbing : Ir. Arianto Santoso, MSc ,
Current pumping system is responsible for nearly 20% of the world electrical energy and energy usage in certain industrial plant operations ranges from 25-50% (U.S. DOE, 2004). So it is very important to choose pump that eficience for any case. In the election of the pump should be noted and taken into account the performance characteristics of the pump. To get the characteristics of the pump needs to be done examining the performance characteristics of the pump with modeling. In this graduate work done modeling of the pump EZ 200 centrifugal pump which is the horizontal radial wing, with the type volut, suction tip and impeler closed. The results of the modeling will then be compared with results from tests that have been done before by brother Widi E P. Modeling pump done on rotation pump constant and flow changing. Rotation pump is 1270 RPM, 1450 RPM, 1650 RPM and 2900 RPM. Flow settings adjusted flow data obtained in testing. From the results of modeling, the highest pump efficiency was obtained at 1450 RPM rotation and flow 0.0063 m 3 / s. Working point of optimum pump at 1450 RPM rotation is 13 m with head at 13 m and flow at 0.0063 m3 / s.